2003
DOI: 10.1081/ese-120023329
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Organic Substances and Reactive Dye in an Immobilized-Cell Sequencing Batch Reactor Operation on Simulated Textile Wastewater

Abstract: Textile wastewater generally consists of high organic substances and is strongly colored. Reactive dye has been used extensively in the textile industries. It is water soluble and difficult to remove by chemical coagulation. Removal of organic substances simultaneously with dye can be achieved by a biological process. This study aims to investigate the treatability of the organic substances and reactive dye in immobilized-cell sequencing batch reactors (SBR). Three different supporting medias namely activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…These results suggest that the 17 day was optimum SRT for the activity of microorganisms (see Figure 5). Similar studies [44,45] have obtained high COD removal efficiencies at the 12 and 15 day of SRT.…”
Section: Effect Of Hrt and F/m Ratio In Csar Reactorsupporting
confidence: 59%
“…These results suggest that the 17 day was optimum SRT for the activity of microorganisms (see Figure 5). Similar studies [44,45] have obtained high COD removal efficiencies at the 12 and 15 day of SRT.…”
Section: Effect Of Hrt and F/m Ratio In Csar Reactorsupporting
confidence: 59%
“…Similarly, better color and COD removal were observed at 15 days SRT compared to 10 days SRT in SBR [37]. Moreover, Pasukphan concluded that increasing sludge age from 12 to 22 days resulted in an increase of COD and color removal [41]. The results of this study indicated that at least 15 days sludge retention time is required for efficient decolorization of Remazol Rot RR and COD removal in SBR system.…”
Section: Discussionmentioning
confidence: 65%
“…Low initial COD concentration (500 mg l −1 ) and dyestuff concentrations (10 mg l −1 ) or longer anaerobic period (18 h) could be the main reasons for better COD removal compared to the results of this study. Over 80% COD removal in total of SBR was observed by Pasukphun and Vinitnantharat [41]. However, there are also reports about no efficient COD removal in anaerobic phase of SBR system.…”
Section: Effect Of Sludge Age On Color and Cod Removalmentioning
confidence: 91%
See 2 more Smart Citations